(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
The heterogeneous contents of various rhynchonellid families indicate that their definition is either loose or insufficient, and opens the door to diverse and sometimes contradictory interpretations. The family Hebetoechiidae Havlíček, 1960 is one of them. Its diagnosis is revised. Some genera included in it at one time or another are assigned to the following new families: Lanceomyoniidae, Ktenopotamorhynchidae, and Eucharitinidae. A new genus, Ktenopotamorhynchus, with type species K. borealiformis (Siemiradzki, 1906a) is proposed, and the genus Lanceomyonia Havlíček, 1960 is revised.